On the equivalence between Bayesian and dominant strategy implementation: The case of correlated types - Alexey Kushnir (University of Zurich, Department of Economics, 2013)
We consider general social choice environments with private values and correlated types. Each agent's matrix of conditional probabilities satisfies the full rank condition. We show that for any Bayesian incentive compatible mechanism there exists a dominant strategy incentive compatible mechanism that delivers the same interim expected utilities to all agents and generates at least the same social surplus. In addition, if there is a social alternative that is inferior to the other alternatives for all agents the dominant strategy incentive compatible mechanism matches exactly the social surplus. These results extend to environments with interdependent values satisfying the single crossing condition.
Keywords: D82; 330; mechanism design; Bayesian implementation; dominant strategy implementation; full surplus extraction; correlation